A retrospective review in the management of T3 laryngeal squamous cell carcinoma: an expanding indication for transoral laser microsurgery. Issue 1 (December 2016) - Butler, A.; Rigby, M.; Scott, J.; Trites, J.; Hart, R.; Taylor, S.
Abstract Background The purpose of this study was to evaluate the functional and oncological outcomes of patients treated for T3 laryngeal squamous cell carcinoma. Specifically comparing transoral laser microsurgery and radiotherapy/chemoradiotherapy treatment modalities. Method A retrospective review of patients treated for T3 laryngeal SCC between 2002 and 2010 was undertaken. Results Forty-nine patients were included. 15 cases were glottic, (9 treated with TLM, 6 with RT/CRT), 33 supraglottic (6 treated with TLM, 27 with RT/CRT) and 1 subglottic subsite (treated with RT/CRT). There was no statistical difference between treatment groups for 24 month locoregional control (72.3 %), overall survival (glottis 86.7 %, supraglottic 70.4 %) and disease specific survival (glottic 93.3 % and supraglottic 74.1 %). Overall laryngeal preservation (84.9 %) was also similar in both groups. Conclusion Our institution is expanding the application of TLM to selected patients with T3 laryngeal carcinoma. Oncological outcomes have not been jeopardized by this approach and the treatment is well tolerated by patients with few complications.